Where did the footnote go? How the change of mode in sight translation affects meaning-making - Randi Havnen (JoSTrans: The Journal of Specialised Translation)
This study investigates how interpreters affect meaning making when translating a written text into speech. The analyses are based on Halliday's theory of linguistic metafunctions from a multimodal perspective. The data are obtained from a strictly controlled design that isolated textual factors related to typical written resources other than language to explore how interpreters addressed them. By placing sight translation in Kress and van Leeuwen's model of the four domains of meaning-making – discourse, design, production and distribution – the interpreter becomes a contributor as a re-producer and a re-distributor, adding more layers to the meaning-making process. Findings reveal that the interpreters vary in how they adapt the text to the spoken mode, and that their exploitation of semiotic resources affect the meaning potential. Although the interpreter´s code of ethics advises against altering the meaning potential, the findings show that such shift is unavoidable because of the modal shift. This study contributes with new insight about semiotic differences in written and spoken texts and shows that meaning potential related to all metafunctions changes through the sight translation process. This change is most evident at the interpersonal level in face-to-face encounters. These new insights should inform interpreters' sight translation practice and training, as well as future research.